2019
DOI: 10.31234/osf.io/2rph5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan, Lovelett, Phun, and Rickard (2019) Systematic and random interleaving for second language learning (preprint)

Abstract: Repeatedly switching between a series of to-be-learned topics, also called interleaved practice (interleaving), can improve learning over traditional, one-topic-at-a-time blocked practice (blocking). We investigated whether interleaving’s benefits for foreign language learning are facilitated by random schedules, wherein training trials follow unpredictable patterns, or systematically alternating schedules, wherein trials are predictably sorted. Students learned to conjugate Spanish verbs in the preterite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, if training involves randomized practice problems and especially if there is a constraint against any problem category appearing multiple times in succession, then (c) a strategy of reusing solutions across successive trials is rendered ineffective, as is (d) the use of any feedback from a given trial as a hint for the next (Lee & Simon, 2004). Consequently, randomly interleaved practice exercises require more memory retrieval and may yield better learning (Carpenter & Mueller, 2013; Pan, 2015; Rohrer, 2012). However, some researchers have also suggested that randomization can be too confusing and generates cognitive overload, particularly in novice learners (Wulf & Shea, 2002).…”
Section: Random Versus Systematically Alternating Schedulesmentioning
confidence: 99%
“…Additionally, if training involves randomized practice problems and especially if there is a constraint against any problem category appearing multiple times in succession, then (c) a strategy of reusing solutions across successive trials is rendered ineffective, as is (d) the use of any feedback from a given trial as a hint for the next (Lee & Simon, 2004). Consequently, randomly interleaved practice exercises require more memory retrieval and may yield better learning (Carpenter & Mueller, 2013; Pan, 2015; Rohrer, 2012). However, some researchers have also suggested that randomization can be too confusing and generates cognitive overload, particularly in novice learners (Wulf & Shea, 2002).…”
Section: Random Versus Systematically Alternating Schedulesmentioning
confidence: 99%